2015
DOI: 10.1086/680187
|View full text |Cite
|
Sign up to set email alerts
|

Moderation from Bias: A Field Experiment on Partisan Media in a New Democracy

Abstract: /Faculty-Bio.aspx?idp177. 2. Our focus is on media effects not choice, though we discuss later why selective exposure (another consequence of motivated reasoning) is likely less common postliberalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Parties have youth wings and women’s wings, as well as local offices or meeting spots in villages or city neighborhoods. They utilize radio and newspaper media (Conroy-Krutz and Moehler 2013). The party leadership make appeals to members to act like a team to strengthen the party mission of getting elected—appeals to turn out to vote, to go to rallies and party meetings, wear party paraphernalia, to protect the ballot boxes from cheaters in the other party, etc 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Parties have youth wings and women’s wings, as well as local offices or meeting spots in villages or city neighborhoods. They utilize radio and newspaper media (Conroy-Krutz and Moehler 2013). The party leadership make appeals to members to act like a team to strengthen the party mission of getting elected—appeals to turn out to vote, to go to rallies and party meetings, wear party paraphernalia, to protect the ballot boxes from cheaters in the other party, etc 16 .…”
Section: Methodsmentioning
confidence: 99%
“…In an experimental setting, Knobloch-Westerwick and Johnson (2014) demonstrated that participants who had been exposed to congruent content online assessed the likelihood of participating in politics at a future time more positively. Finally, in a field experiment manipulating the ideological content to which Ghanan public-transportation passengers were exposed, Conroy- Krutz and Moehler (2015) showed that incongruent exposure decreased participation whereas exposure to congruent content had no influence on it. Similar patterns can be found in work focusing on the influence of discussion network heterogeneity on participation.…”
Section: Partisan Media and Political Participationmentioning
confidence: 99%
“…These biases have been addressed in some of social science's most creative observational studies, although these approaches are well suited to answering certain questions (such as those for which instruments are available) but not others [e.g., (25)(26)(27)(28)(29)(30)(31)(32)]. The biases are also addressed via elegant experiments and quasi-experiments, often made possible by studying different quantities of interest, such as individual-level effects or occasionally the effects on aspects of the national conversation (26,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
mentioning
confidence: 99%